Multiple molecular detection of respiratory viruses and associated signs of airway inflammation in racehorses - Doubli-Bounoua, Nadia (Virol J, 2016)
BACKGROUND: The potential involvement of viruses in inflammatory airway disease (IAD) was previously investigated through either serology or PCR from nasopharyngeal swabs (NS). The aims of this study were to determine the prevalence and incidence of viral genome detection by qPCR in the equine airways, and their association with respiratory clinical signs. METHODS: Both NS and tracheal washes (TW) were collected monthly on 52 Standardbred racehorses at training, over 27 consecutive months (581 samples). Equid herpesviruses (EHV)-1, −4, −2 and −5, equine rhinitis virus-A and -B (ERBV), equine adenovirus-1 and −2, equine coronavirus and equine influenza virus were systematically investigated in both NS and TW. Nasal discharge, coughing, tracheal mucus score and TW neutrophil proportions were simultaneously recorded. RESULTS: Genome for 7/10 viruses were detected at least once throughout the study; up to 4 different viruses being also concomitantly detected. Monthly incidence in TW was respectively 27.9% (EHV-5), 24.8% (EHV-2), 7.1% (ERBV), 3.8% (EHV-4), 1.9% (EAdV1) and 0.2% (EHV-1; ERAV). Neither agreement nor correlation between NS and TW was found for respectively genome detection and viral loads. Detection of viral genome in NS was not associated with any clinical sign. Coughing was significantly associated with TW detection of EHV-2 DNA (OR 3.1; P = 0.01) and ERBV RNA (OR 5.3; P < 0.001). Detection of EHV-2 DNA in TW was also significantly associated with excess tracheal mucus (OR 2.1; P = 0.02). CONCLUSIONS: Detection and quantification of EHV-2 and ERBV by qPCR in TW, but not in NS, should be considered when investigating horses with IAD. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12985-016-0657-5) contains supplementary material, which is available to authorized users.